2018
DOI: 10.1111/epi.14636
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a genetic effect in altered cortical surface area but not in cortical thinning in siblings of patients with mesial temporal lobe epilepsy

Abstract: Although studies have shown cortical and subcortical changes in first-degree relatives of patients with familial forms of temporal lobe epilepsy, few studies have addressed extrahippocampal morphology changes in unaffected siblings of patients with sporadic mesial temporal lobe epilepsy with hippocampal sclerosis (MTLE-HS). Alhusaini et al 1 described subtle reduced cortical volumes in the anteromedial temporal cortex of asymptomatic siblings of sporadic MTLE-HS patients, suggesting that such localized traits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…While mTLE is generally thought of as an acquired disorder, there is emerging evidence for a genetic link in sporadic mTLE, 5,6 and studies have found alterations in structural brain morphology in asymptomatic relatives of patients with HS 7,8 . This structural alteration in asymptomatic relatives suggests an inherited trait that precedes seizure onset 9 …”
Section: Introductionmentioning
confidence: 99%
“…While mTLE is generally thought of as an acquired disorder, there is emerging evidence for a genetic link in sporadic mTLE, 5,6 and studies have found alterations in structural brain morphology in asymptomatic relatives of patients with HS 7,8 . This structural alteration in asymptomatic relatives suggests an inherited trait that precedes seizure onset 9 …”
Section: Introductionmentioning
confidence: 99%